O abate de frangos pelo método Kosher: definições, conjuntura de mercado e perspectivas de estudo - Izidoro, Thiago Braga [UNESP]; Pereira, Juliano Gonçalves [UNESP]; Soares, Vanessa Mendonça [UNESP]; Spina, Thiago Luiz de Belém [UNESP]; Pinto, José Paes de Almeida Nogueira [UNESP] (My University, 2012)
Kosher food is understood as being the appropriate one for a Jew, ensuring this way their physical and spiritual health. It follows a series of food standards contained in the Halakha, which is a set of laws governing the proper moral conduct of the Jewish culture. Currently the market for Kosher food moves about 200 billion dollars in the USA, with consumers not only among Jews, but also among Muslims, vegetarians and people who associate such products with a more rigorous quality control. To be considered Kosher, a product has to go through some changes in its production flowchart, being the slaughter of chickens one of the most modified compared to the conventional method. Given the importance of the subject, new lines of research have emerged in order to determinate how the insertion or the alteration in the flowchart steps practiced in the Kosher food industry influence the food overall quality and safety.

Se entiende por alimento Kosher a aquel que es considerado más apropiado por un judío, garantizando su salud física y espiritual. Tales alimentos siguen una serie de leyes estipuladas en el Halajá, el cual es un conjunto de estatutos que gobierna la conducta moral apropiada en la cultura judía. Actualmente el mercado para comida Kosher mueve alrededor de 200 mil millones de dólares en los Estados Unidos de América siendo los consumidores no solamente judíos, sino también musulmanes, vegetarianos y personas que asocian tales productos a un control de calidad más riguroso. Para ser considerado Kosher, un producto tiene que pasar por algunos cambios en su diagrama de flujo. Entre estos, uno de los más importantes con relación al método convencional es el sacrificio de pollo. Dada la importancia del tema, han surgido nuevas líneas de investigación con el fin de determinar como la inserción o la alteración en las etapas del diagrama de flujo industrial para alimentos Kosher influye en la seguridad y calidad de estos alimentos en general.

Entende-se por alimento Kosher aquele apropriado a um judeu, garantindo sua saúde física e espiritual. Tais alimentos seguem uma série de normas contidas na Halacha, que é um conjunto de leis que regem a conduta moral adequada da cultura judaica. Atualmente o mercado de alimentos Kosher movimenta cerca de 200 bilhões de dólares nos EUA, tendo como público consumidor não apenas judeus, mas também muçulmanos, vegetarianos e pessoas que associam tais produtos a um controle de qualidade mais rigoroso. Para que um alimento se torne Kosher, na prática, ocorre alteração do respectivo fluxograma de produção, sendo o abate de frangos um dos mais modificados em relação ao método convencional. Diante da relevância do assunto, novas linhas de pesquisa emergiram com o intuito de diagnosticar como a inserção ou alteração de etapas no fluxograma industrial de alimentos Kosher influenciam a qualidade geral e a inocuidade dos alimentos.
The slaughter of chickens by the Kosher method: definitions, market situation and prospects of study
Sacrificio de pollo mediante el método Kosher: definiciones, mercado y perspectivas de estúdio
Keywords: Chicken slaughter; Kosher; Food industry; Food salting process; Kosher; Industria de alimentos; Sacrificio de pollos; Salazón de alimentos; Abate de frangos; Kosher; Indústria alimentícia; Salga